Phytoremediation: an option for removal of organic xenobiotics from water - Dordio, Ana V. (2012)
Pollution by persistent organic pollutants (pesticides, pharmaceuticals, petroleum hydrocarbons, PAHs, PCBs, etc.) is an environmental problem that is recognized worldwide. In order to address this problem, cost effective technologies have been developed and evaluated for the decontamination of soil and water resources. Phytoremediation is a promising technology that uses plants and the associated rhizosphere microorganisms to remove, transform/detoxify, or accumulate organic and inorganic pollutants present in soils, sediments, surface or ground water, wastewater, and even the atmosphere. In fact, as a result of their sedentary nature, plants have evolved diverse abilities for dealing with toxic compounds in their environment. They, therefore, possess a variety of pollutant attenuation mechanisms that makes their use in remediating contaminated land and water more feasible than physical and chemical remediation. Currently, phytoremediation is used for treating many classes of organic xenobiotics including petroleum hydrocarbons, chlorinated solvents, polycyclic aromatic hydrocarbons, pesticides, explosives, pharmaceutical compounds and their metabolites, and it involves several decontamination mechanisms. There are several different types of phytotechnologies such as, for instance, treatment constructed wetlands. The aim of this work is to present a review on the application of phytoremediation technologies for water decontamination from persistent organic pollutants, with special emphasis focused on the removal of a class of emergent pollutants that has recently been receiving a lot of attention, the pharmaceutically active compounds. Within the realm of phytotechnologies, constructed wetlands for wastewater treatment are dedicated a special focus as these systems have been used with success for the removal of several different types of organic xenobiotics.